International developments and prospects for the 21st century - McKenzie, Mark-Anthony ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Reviews the level of Caribbean central banks' independence. Looks at issues relating to a Caribbean Monetary Union and the link between monetary arrangements. Examines whether or not the financial sector supervisory function should be separated from central banks in the Caribbean.